The effect of adding L-Carnitine to the GnRH-antagonist protocol on assisted reproductive technology outcome in women with polycystic ovarian syndrome: a randomized clinical trial - Arezoo Sheida; Robab Davar; Nasim Tabibnejad; Maryam Eftekhar (Taylor & Francis Group, 2023)
Objective This study aimed to investigate the effect of adding L-Carnitine to the gonadotropins on ART outcome in frozen-thawed embryo transfer cycles among PCOS women.Methods In this randomized clinical trial, 83 patients with PCOS were randomized to either L-Carnitine supplemented (n = 42) or control (n = 41) groups. The L-Carnitine group was given 3000 mg of oral L-Carnitine daily until the final day of ovulation. The numbers of metaphase II (MII) oocytes, 2-pronuclears (2PNs), oocyte maturity rate, fertilization rate, fertilization proportion as well as implantation, chemical and clinical pregnancy rates were compared between the two groups.Results Even though the duration of stimulation and endometrial thickness were comparable between groups (p > .05), serum estradiol level on the day of oocyte triggering, was significantly higher in the L-Carnitine group compared to the control group (p < .05). In contrast, the number of retrieved and MII oocytes as well as the number of 2PNs and obtained embryos were similar between groups (p > .05). Moreover, oocyte maturity rate (0.85 ± 0.38 vs. 1.02 ± 0.90), fertilization proportion (0.62 ± 0.44 vs. 0.80 ± 0.86), fertilization rate (0.70 ± 0.22 vs. 0.76 ± 0.19) along with implantation rate (18.1 vs. 13.7%), chemical (26.8 vs. 30.7%) and clinical (24.3 vs. 25.6%) pregnancy rates, were all comparable between L-Carnitine and control groups respectively (p > .05).Conclusions Our result showed that oral L-Carnitine administration during induction of ovulation among PCOS women could not improve laboratory and pregnancy outcome.